1988
DOI: 10.1002/bbpc.198800287
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Shear Viscosity of Nitro‐benzene/Isooctane Mixtures in the Critical Region

Abstract: Critical Phenomena / Liquids / Phase Transitions / ViscosityResults of measurements of the temperature dependence of shear viscosity of seven nitro-benzene/isooctane mixtures of different compositions in the critical region are reported. The analysis of the viscosity data of the mixture of the critical composition in terms of critical exponent gives a value of c/J~= 0.048 ± 0.001. It is higher by about 20% than the theoretical value based on dynamic renormalization group theory calculations. The shear viscosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Experiments on molecular systems indicate a very small critical exponent for the zero shear and zero frequency shear viscosity, [1][2][3][4] or a logarithmic divergence, 5 although in a few papers it is shown that the experimental accuracy is not sufficient to distinguish between the two. [6][7][8] It is also reported that neither an exponential nor logarithmic divergence occurs, but that the viscosity remains finite at the critical point.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments on molecular systems indicate a very small critical exponent for the zero shear and zero frequency shear viscosity, [1][2][3][4] or a logarithmic divergence, 5 although in a few papers it is shown that the experimental accuracy is not sufficient to distinguish between the two. [6][7][8] It is also reported that neither an exponential nor logarithmic divergence occurs, but that the viscosity remains finite at the critical point.…”
Section: Introductionmentioning
confidence: 99%